Analisis Perkembangan Kurikulum Terhadap Kualitas Pendidikan di Indonesia - Mukhlisa (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The national education goal in Indonesia is to create a society that is religious, moral, knowledgeable, and skilled. Moreover, the system aims to produce individuals who are physically and spiritually healthy, possess strong character, and carry a sense of responsibility. To realize these aspirations, curriculum development plays a central role in shaping the direction and quality of education. One of the inseparable aspects of advancing the national education system is policy-making related to curriculum design and implementation. As a critical component of education, the curriculum holds a strategic position and significantly influences the overall quality of learning outcomes. This study aims to analyze the impact of curriculum development on the quality of education in Indonesia. Using a qualitative approach, the research is based on a literature review involving academic publications, government documents, and relevant policy reports. The findings suggest that curriculum changes can have both positive and negative effects on education quality, depending on how well the curriculum aligns with the needs of learners, educators, and national goals. Positive impacts include the enhancement of learning competencies, adaptability to global challenges, and the promotion of holistic student development. On the other hand, challenges arise when curriculum reforms are implemented hastily or without adequate support for teachers and institutions. Therefore, curriculum development must be based on comprehensive planning and supported by effective policy implementation to improve the quality of education sustainably.